Conservative inpatient treatment for affections of distal bone metaepiphyses of the forearm - Bets, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The article describes data about giving aid to 38 patients with affections of distal bone metaepiphyses of the forearm, who were sent to hospital for surgical treatment following unsuccessful attempts of closed repositions of fragments at the outpatient stage. Causes of negative results are analysed. By means of suggested tactical and radiological approaches, 23 of 38 patients managed to avoid surgical treatment.